English Online Teaching for Elementary Students in Covid-19 Pandemic Era at Perum. Kresna Asri Wagir - Masrurotul Ajiza; Nanik Rahman Astuti (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2022)
The Covid-19 pandemic has had such a huge impact on various aspects of life globally, including the world of education. This has resulted in students from elementary school to university having to study from home or what is known as online learning. Of course, this learning is not easy to implement, especially for elementary school (SD) students. In contrast to junior high school students or higher, elementary school students are seen as the most difficult to accept online learning for several reasons, including: 1) difficulties in using gadgets and lack of concentration in learning, 2) lack of motivation to do online learning, 3) difficulties in learning. understand the lessons given by their teacher due to limited space and time to get the opportunity to ask the teacher. The English language learning in this activity is carried out face-to-face. Learning is carried out for approximately 6 months using 2 teachers. In addition to focusing on teaching English, the activity also provides knowledge to students in mastering the use of technology, such as cellphones and laptops. The results of learning English to elementary school students at Perum. Kresna Asri Wagir during the Covid-19 pandemic was very helpful for students and parents who had been experiencing difficulties in learning English.